Analisis Kerjasama Bagi Hasil Petani Tambak pada Akad Muzara'ah (Studi Kasus pada Petani Tambak di Desa Tajung Widoro, Kecamatan Bungah, Kabupaten Gresik) - Nuzulus Sakinah; Muhammad Ala'uddin; Niswatun Hasanah (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
The profit-sharing cooperation practice in pond farming in Tajung Widoro Village, Bungah District, Gresik Regency, has been carried out for generations and is based on verbal agreements without written contracts. This study aims to describe the mechanism of profit-sharing cooperation among fish pond farmers and to analyze its conformity with the muzara'ah contract. The research employed a qualitative approach with a descriptive-analytical research type, using in-depth interviews with pond owners, pond managers, a community leader, and a religious leader, supported by direct field observation. The findings indicate that the profit-sharing cooperation in Tajung Widoro Village is conducted verbally with profit-sharing ratios of 75:25 and 90:10. All production capital is borne by the pond owners, and there is a practice known as Welasan, a voluntary contribution given to managers when crop failure occurs. Overall, the practice fulfills the pillars and conditions of the muzara'ah contract according to the perspective of Islamic jurisprudence (fiqh muamalah), while Welasan is best understood as a form of shadaqah reflecting social concern and mutual assistance (ta'awun) within the pond farming community